2009
DOI: 10.1080/13632750802655687
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned: student voice at a school for pupils experiencing social, emotional and behavioural difficulties

Abstract: Student voice and pupil empowerment projects are common in many mainstream schools. However, such initiatives are more challenging to implement in provision for students experiencing (social), emotional and behavioural difficulties (SEBD). As a consequence, they are less frequently attempted. This article reports one such attempt at an SEBD special school, where a student research group was formed to evaluate the school's behaviour policy. The students' views remind professionals of the need for consistency, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 24 publications
3
43
0
8
Order By: Relevance
“…This involved positioning themselves and others across different space and time contexts, recognising others as significant for their lives and well-being, defining themselves as individuals with specific experiences and backgrounds, and constructing, maintaining and contesting the cultural practices of what it means to have authorship in their social settings in and outside school. These discourses have been identified as pivotal in contributing to children's formation of their sense of agency (Emirbayer & Mische, 1998) and, more broadly, to their socioemotional well-being (Cooper & Cefai, 2009;Kim-Cohen et al, 2004;Sellman, 2009;Timimi & Maitra, 2006). Here, the children are invited to move between the past, the present and the future in composing their life stories and significant events in them.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This involved positioning themselves and others across different space and time contexts, recognising others as significant for their lives and well-being, defining themselves as individuals with specific experiences and backgrounds, and constructing, maintaining and contesting the cultural practices of what it means to have authorship in their social settings in and outside school. These discourses have been identified as pivotal in contributing to children's formation of their sense of agency (Emirbayer & Mische, 1998) and, more broadly, to their socioemotional well-being (Cooper & Cefai, 2009;Kim-Cohen et al, 2004;Sellman, 2009;Timimi & Maitra, 2006). Here, the children are invited to move between the past, the present and the future in composing their life stories and significant events in them.…”
Section: Discussionmentioning
confidence: 96%
“…Through agentic experiences, and recognising them, children can learn to trust their own agency to act in different situations (see, e.g. Johnson, 2008;McLaughlin, 2008;Olh et al, 2012;Sellman, 2009;Weare, 2010). These arguments are also supported by studies of efficacy showing 'that young children are not merely passive recipients of the socializing 212…”
Section: Introductionmentioning
confidence: 98%
“…To compound these difficulties, students with EBD have their voices heard the least, are empowered the least, and are the least liked group of students (Baker, 2005;Cooper, 2006;Lewis & Burman, 2008). With all of these obstacles to success, students with EBD have indicated that the relationship that they have with teachers is one of the most important factors in their success (Cefai & Cooper, 2010;Garner, 1993;Harris, Vincent, Thomson, & Toalster, 2006;Jahnukainen 2001;Pear, 1997;Sellman, 2009;).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rhetoric is often about children having an 'authentic voice,' when, in reality, they are being manipulated into accepting and responding in prescribed ways to adult classifications of types of pupil and behaviour (Sellman, 2009). Practice is most problematic when children are encouraged to share personal feelings and emotions which others can easily use to make them feel uncomfortable, and particularly when unwanted behaviour is being discussed according to the principles of restorative justice.…”
Section: Discussionmentioning
confidence: 99%